Accounting Evaluation: Digital Transformation as Moderating Variable in Fintech, Green Finance, And Blue Finance Impact on Banking Financial Performance - Gumilang, Risa Ratna; Nugraha, N; Suryadi, Edi; Sari, Maya; Heryana, Toni (Jurnal ASET (Akuntansi Riset), 2025)
This study aims to examine the influence of fintech adaptation, green finance and blue finance on financial performance moderated by digital transformation. The research was conducted on banking sub sector companies listed on the Indonesia Stock Exchange (IDX) for the period of 2021-2023, totalling 141 observation data. The research results using WRAP PLS analysis found that fintech adaptation and green finance do not affect financial performance while blue finance has a significant impact on financial performance. Furthermore, the moderation test results showed that digital transformation moderates the effect of fintech adaptation and green finance on financial performance, but does not moderate the effect of blue finance on financial performance. The research findings support stakeholder’s theory, indicating that banks must play a role in providing policy support to the government in realizing environmentally-oriented investments.